The history of palaeoflood and palaeoclimate recorded in the flood deposits of the Kherlen River, Mongolia. (8th June 2017) - Kim, Song-Hyun; Tanaka, Yukiya; Kashima, Kaoru
Abstract: This study examines the 1500-year history of massive floods as recorded in the slackwater deposits of the Kherlen River basin in Mongolia. The study area is located along the Kherlen River in Baganuur district, Ulaanbaatar. Site HL1 has a flood frequency of 89 years and an accumulation rate of 1.2 mm/y over approximately 1500 years. Site HL2 has a flood frequency of 72.2 years and an accumulation rate of 1.46 mm/y during about 700 years. The range of calculated value for flood frequency and annual accumulation rate during the period of the 10th century to the early 20th century at site HL1 is entirely different from that in other periods. It is considered that the palaeohydrological environment of the study site during that time might have been influenced by climatic change as well as geomorphological and hydrological change. Based on the results of identification of discrete flooding and age dating ( 137 Cs and 14 C), the sedimentary layers of HL1 and HL2 were divided into 4 periods (period 1: 1960–2012, period 2: 970–1960, period 3: 533–970, period 4: 427–533) and 2 periods (period 1: 1960–2012, period 2: 1290–1960), respectively. The authors suggest that the past climate of the region was greatly influenced by the East Asia summer monsoon. It is suggested that the occurrence of the large-scale floods in eastern Mongolia was influenced by the strengthening and weakening of the summer monsoon due to climate change.